Preventive Conservation, Treatment, and Technical Study of Plasticized Poly(vinyl chloride) Multiples by Joseph Beuys. (3rd April 2023) - Ledoux, Nicole; Rayner, Georgina; Costello, Susan; Chang, Angela
ABSTRACT: Works of art made of plasticized poly(vinyl chloride) (PVC) present unique and pressing conservation challenges. Due to inherently unstable formulations, PVC can deteriorate rapidly, producing dramatic alterations that were unanticipated by artists and collectors. This is the case for three works by Joseph Beuys with PVC components in the Harvard Art Museums' collection: Phosphorus-Cross Sled, Postcards 1968–1974, and Stamp Sculpture . Over the course of the last two decades, exudation of liquid plasticizer and progressive discoloration of the PVC was observed and appeared to be worsening with time. This paper presents the results of research undertaken since 2012 to develop storage and display guidelines that will slow the deterioration and improve the accessibility of these works. The three objects under study are all multiples, meaning that they were released in editions, which are now dispersed across numerous museums and private collections. Analysis using gas chromatography-mass spectrometry (GC-MS, with and without pyrolysis) and scanning electron microscopy with energy dispersive X-ray (SEM-EDX) spectroscopy has identified variability in the PVC formulation and exudate across different multiples, suggesting that they may derive from different manufacturing batches. Experimental testing of PVC material from Beuys's studio has shown that sealed Mylar enclosures and storage at temperatures between 4.4 and 12.8 °C are effective in slowing the migration of plasticizer to the surface. After implementing these changes to the housing and storage of the PVC postcard from Postcards 1968–1974, reabsorption of plasticizer exudate was observed, demonstrating that reversal of the plasticizer migration is possible under these conditions.